Intervening Role of Metacognition to Improve Task performance in Prospective Teachers: An Experimental Study - Siddiqui, Ghazal Khalid; Lodhi, Huma; Kalsoom, Tahira (Journal of Arts & Social Sciences, 2020)
The teachers are trained with the aim to provide the necessary knowledge and skills that could help them in dealing with difficulties that they face during teaching, from the planning of a lesson to its implementation. All those skills could be developed among prospective teachers during the phase of their learning. The current study was supposeded to assess the implementation of such skills in classrooms and then measure its effect on the students’ performance. For this purpose, a quasi-experiment was carried out. Consequently, two intact groups enrolled in the third semester of B.Ed. honors at a public university were considered as a sample of the study. Metacognitive Awareness Inventory (MAI) by Schraw and Dennison (1994) was adapted to test Metacognition. Parallel to this, the researcher developed rubrics and observation sheets to assess students’ performance of tasks. Results of the current research reflected that metacognition development has a significant effect on the task performance of students who received the intervention. In light of these results, it is suggested that teacher training institutes should consider the development of Metacognition among their students. Teachers should incorporate different techniques that help them in inculcate metacognition development among their students.